Influence of buffer electrolyte and ph on the electrochemical performance of glucose oxidase-laccase biofuel cell - Asrul, Nurrisa; Othman, Raihan; Mohd. Salleh, Hamzah; Ali, Mohammad Nazri (American Scientific Publishers, 2013)
We investigate the influence of buffer electrolyte and pH on the electrochemical performance of glucose oxidase-laccase biofuel cell (BFC). A simplified system design is adopted i.e. we employ freely-suspended glucose oxidase and laccase enzymes. The BFC comprises nickel mesh as the oxidative current collector and a carbon-based air electrode as the reductive current collector, enclosed in acrylic casing of 3 ml volumetric capacity. The air electrode also serves as the ambient oxygen diffusion site to continuously feed oxygen into the system. Three types of anolyte/catholyte buffer electrolyte are studied – citrate/citrate, phosphate/phosphate and citrate/phosphate, in the pH range 5 – 6.5. A biocatalytic electrochemical system is highly sensitive. Consequently, any variation in the electrolyte formulation would affect the cell discharge performance. Thus, we utilize the discharge profile capacity of the BFC to elucidate the optimum electrolyte formulation. Though the approach is indirect, the observed changes are obvious, suggesting the method is viable. It is found that the citrate/citrate buffer electrolyte of pH 5 exhibits the highest power output of 1074 mWh or volumetric power density of 1.7 Wh/l. The cell is able to sustain continuous discharge current of 30µA for about 31.75 hours with operating voltage around 1.0 V, in an uncontrolled open environment. Interestingly, the observed discharge performance and power density are comparable to BFC employing immobilized enzymes and mediators, in a controlled environment.